Novel tungsten stabilizing SrCo1−xWxO3−δ membranes for oxygen production - Chan, J.; Zhang, K.; Zhang, C.; Tian, H.; Liu, Shaomin (Elsevier Ltd, 2015)
Mixed conducting perovskite membranes have the potentials to replace the conventional expensive cryogenic method to separate oxygen from air and improve the viabilities of these clean energy technologies which need pure oxygen as the feed gas. In this paper, a series of SrCo1−xWxO3−δ (x=0.05–0.2) perovskite membranes were synthesized and characterized for their potential in oxygen separation. The crystal structure and oxygen permeation flux of the membranes were systematically investigated. Due to the enhancement of phase stability by tungsten doping, the preferred cubic perovskite structure at lower temperature is successfully obtained and maintained at the doping concentration from 5% to 10%. However, the further doping increase leads to the formation of other crystal phase unfavorable for oxygen permeation. The tungsten doping concentration also exerts significant effects on the oxygen permeability of the resultant membranes. SrCo0.9Wx0.1O3−δ exhibited the highest oxygen permeation flux among the tested samples, and reached a flux value up to 2.6 ml cm−2 min−1 at 900 °C under an air/helium oxygen gradient for a 1 mm thick membrane, comparing favorably with the best membrane ever-reported. Long-term operation test also signals the excellent permeation stability under operating conditions.